Analisis Hak Recall Partai Politik Terhadap Anggota Dewan Perwakilan Rakyat - Yunus, Rahmawati (Universitas Proklamasi 45, 2025)
The recall right of political parties against members of the House of Representatives (DPR) in Indonesia is regulated in Article 239 paragraph (2) of Law Number 17/2014. The recall mechanism allows for the removal of members of the House of Representatives who are not in line with party policy, even though these members were directly elected by the people. This can shift popular sovereignty as it does not provide space for constituents to be involved in the recall process and can reduce the accountability of DPR members to their voters. The research focuses on the mechanism of recall rights of political parties against members of the House of Representatives based on the People's Sovereignty. Through a normative inquiry, this research analyzes the provisions on the implementation of the recall right mechanism by political parties against members of the House of Representatives based on People's Sovereignty. The author finds that members of the House of Representatives can be dismissed intermittently if they are absent for three months without information, violate the oath/pledge or code of ethics, are sentenced to a minimum of five years in prison, are proposed by the party, no longer meet the candidate requirements, violate the provisions, lose party membership, or ally with alternative political groups. The mechanism goes through the stages of submitting proposals to the DPR leadership, the president, and the KPU. This research hopes to contribute understanding of the debate on the mechanism of recall rights of political parties without excluding popular sovereignty.